2014
DOI: 10.1080/15287394.2014.938209
|View full text |Cite
|
Sign up to set email alerts
|

Lead Intoxication Under Environmental Hypoxia Impairs Oral Health

Abstract: We have reported that chronic lead intoxication under hypoxic environment induces alveolar bone loss that can lead to periodontal damage with the subsequent loss of teeth. The aim of the present study was to assess the modification of oral inflammatory parameters involved in the pathogenesis of periodontitis in the same experimental model. In gingival tissue, hypoxia increased inducible nitric oxid synthase (iNOS) activity (p < .01) and meanwhile lead decreased prostaglandin E2 (PGE2) content (p < .05). In sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…Terrizzi et al ., have reported that elevated lead levels under hypoxia induces alveolar bone resorption and periodontitis 47 . More recently they demonstrated that iNOS and PGE 2 levels are altered by lead and hypoxia as inflammatory responses that would contribute to damage of the periodontium 48 . Furthermore, the lead levels investigated in these previous studies generally targeted levels that have been shown in blood to have substantial neurotoxicity (≥10 µg/dL), although levels of >5 µg/dL are considered deleterious 49 .…”
Section: Discussionmentioning
confidence: 99%
“…Terrizzi et al ., have reported that elevated lead levels under hypoxia induces alveolar bone resorption and periodontitis 47 . More recently they demonstrated that iNOS and PGE 2 levels are altered by lead and hypoxia as inflammatory responses that would contribute to damage of the periodontium 48 . Furthermore, the lead levels investigated in these previous studies generally targeted levels that have been shown in blood to have substantial neurotoxicity (≥10 µg/dL), although levels of >5 µg/dL are considered deleterious 49 .…”
Section: Discussionmentioning
confidence: 99%
“…The original premise of the study was based upon data regarding elevated blood lead levels and an increased risk of periodontitis across populations . Thus, we hypothesized that increased lead levels would stimulate proinflammatory responses in cells of the periodontium that might contribute to the biologic dysregulation of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…110,111 The original premise of the study was based upon data regarding elevated blood lead levels and an increased risk of periodontitis across populations. 29,34,36,112,113 Thus, we hypothesized that increased lead levels would stimulate proinflammatory responses in cells of the periodontium that might contribute to the biologic dysregulation of the disease. Interestingly, of the large number of genes involved in host responses, which were expressed by the oral epithelial cells and affected by treatment with biofilms, a rather limited array was altered in expression by environmental lead.…”
Section: Effects Of Environmental Lead On Epithelial Responses To Amentioning
confidence: 99%
See 2 more Smart Citations